Sukcesja władzy cesarskiej w okresie rządów dynastii julijsko-klaudyjskiej (30 p.n.e. – 68 n.e.) - Sawiński, Paweł (Wydawnictwo Naukowe UAM, 2016)
The presented book is focused on the problem of the succession of imperial power at the period of the Julio-Claudian dynasty. In the first part of the thesis, the subject of my analysis is the succession policy of the princeps from the first imperial dynasty. On the grounds of numerous literary texts, numismatic, epigraphic and iconographic sources I am trying to establish what was the role that the separate members of the imperial family had in Augustus’ and his successors’ succession plans. Apart from that, this part of the book also shows how the future successors were introduced to the public and how they were honoured. The second part of the present publication concentrates on the mechanisms of taking over the imperial power during the reign of Julio-Claudian dynasty. Among other things, there has been taken an effort to find out what factors played a decisive role in electing next princeps from the dynasty and, what is more, what the model of appointing a new emperor looked like.

Książka poświęcona jest kwestii sukcesji władzy cesarskiej w okresie rządów pierwszej dynastii cesarskiej. Pomimo że pryncypat nie był formalnie dziedziczną monarchią, to jednak w praktyce obserwujemy wyraźną tendencję do przekazywania władzy cesarskiej w obrębie rodziny panującej. August i jego kolejni następcy prowadzili intensywną politykę sukcesyjną, której celem było przekazanie władzy cesarskiej wybranemu przez nich kandydatowi. W pracy przeanalizowano mechanizmy polityki sukcesyjnej princepsów z dynastii julijsko-klaudyjskiej oraz proces przejmowania władzy cesarskiej przez kolejnych następców Augusta.
Keywords: władza cesarska; polityka sukcesyjna; dynastia julijsko-klaudyjska